2016
DOI: 10.1186/s41065-016-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of genes involved in anthocyanins biosynthesis and transport in berries of black and white spine grapes (Vitis davidii)

Abstract: BackgroundThe color of berry skin is an important economic trait for grape and is essentially determined by the components and content of anthocyanins. The fruit color of Chinese wild grapes is generally black, and the profile of anthocyanins in Chinese wild grapes is significantly different from that of Vitis vinifera. However, V. davidii is the only species that possesses white berry varieties among Chinese wild grape species. Thus, we performed a transcriptomic analysis to compare the difference of transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 92 publications
(171 reference statements)
2
26
0
Order By: Relevance
“…In the current study, the ratio of VviF3 ′ 5 ′ Hs to VviF3 ′ Hs levels in “CS” was significantly and distinctly higher in winter cropping berries during ripening, in parallel with their higher ratio of 3′5′-substituted to 3′-substituted flavonoids, which was presumed to control the flavonoid composition of grape berries. Similarly, a previous study also found that the temporal and variety-specific expression of VviF3 ′ H and VviF3 ′ 5 ′ H in grapes occurred in coordination with the accumulation of the respective hydroxylated metabolites ( Bogs et al, 2006 ; Sun et al, 2016 ).…”
Section: Resultssupporting
confidence: 67%
“…In the current study, the ratio of VviF3 ′ 5 ′ Hs to VviF3 ′ Hs levels in “CS” was significantly and distinctly higher in winter cropping berries during ripening, in parallel with their higher ratio of 3′5′-substituted to 3′-substituted flavonoids, which was presumed to control the flavonoid composition of grape berries. Similarly, a previous study also found that the temporal and variety-specific expression of VviF3 ′ H and VviF3 ′ 5 ′ H in grapes occurred in coordination with the accumulation of the respective hydroxylated metabolites ( Bogs et al, 2006 ; Sun et al, 2016 ).…”
Section: Resultssupporting
confidence: 67%
“…A number of studies about transcriptomics and metabonomics in anthocyanin biosynthesis revealed that the expression levels of structural genes play an important role in anthocyanin accumulation, especially DFR, ANS, and F3H [55][56][57][58]. DFR and ANS are considered as very important enzymes in anthocyanin biosynthesis, as they could direct the flavonoid flux into the anthocyanin branch [55][56][57][58]. Previous studies showed that the expression levels of DFR, ANS, and F3H and some transcription factors were positively correlated with anthocyanin accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The anthocyanins that accumulate in red sweet cherry ‘Tieton’ during the ripening stage are cyanidin-3- O -rutinoside and cyanidin-3- O -glucoside, and these anthocyanins remain at low levels in yellow sweet cherry ‘13–33’ [ 32 ]. In grape, the main anthocyanin is malvidin-3,5- O -diglucoside [ 33 ]. Thus, the types and quantities of anthocyanins differ among different fruit species.…”
Section: Discussionmentioning
confidence: 99%